Cultural competence in caring for Muslim patients - Rassool, G. Hussein (Palgrave Macmillan, 2014)
To meet the care needs of today's diverse patient community, healthcare professionals must learn to care in environments comprising different worldviews, communication styles and expectations. To meet this challenge, it is essential that they operate from a solid foundation of knowledge, based on high standards for cultural competence in nursing practice. Cultural Competence in Caring for Muslim Patients is designed for nurses and allied healthcare professionals. It offers a deeper insight into ways in which the Islamic faith is intertwined with patient care, and explores approaches with which to effectively address the varying healthcare requirements of a growing and diverse Muslim community. Following a clear and accessible format, the book discusses key issues including: the identity and religious beliefs of Muslims; the ethical dimension in caring; understanding the Muslim family system; health considerations during fasting and pilgrimage (Hajj). What's more, case studies, activities and discussion questions throughout actively support learning and reflective practices. This insightful guide will prove a valuable asset for any nurse or healthcare professional looking to develop their understanding of how to deliver culturally compassionate and congruent care.